CORRELATION OF ENDOGENOUS INTOXICATION INDICATORS ON KIDNEY MORPHOLOGY IN SENSITIZED RECIPIENTS AFTER KIDNEY TRANSPLANTATION (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
This article presents a detailed analysis of the results of examination and treatment of 27 recipients with a high degree of sensitization to the transplant. A study of changes in clinical, laboratory and morphological parameters after transplantation was conducted, with an emphasis on their statistical processing and comparison with data from modern scientific publications. The results of the study indicate a close relationship between endogenous intoxication indicators and morphological changes in the transplant, since the identified morphological disorders in the transplant were found in recipients with elevated levels of endogenous intoxication indicators in the blood.